Sphygmomanometers and thermometers as potential fomites of Staphylococcus haemolyticus: biofilm formation in the presence of antibiotics - Bruna Pinto Ribeiro Sued; Paula Marcele Afonso Pereira; Yuri Vieira Faria; Juliana Nunes Ramos; Vanessa Batista Binatti; Kátia Regina Netto dos Santos; Sérgio Henrique Seabra; Raphael Hirata Júnior; Verônica Viana Vieira; Ana Luíza Mattos-Guaraldi; José Augusto Adler Pereira (Memorias do Instituto Oswaldo Cruz)
BACKGROUND The association between Staphylococcus haemolyticus and severe nosocomial infections is increasing. However, the extent to which fomites contribute to the dissemination of this pathogen through patients and hospital wards remains unknown. OBJECTIVES In the present study, sphygmomanometers and thermometers were evaluated as potential fomites of oxacillin-resistant S. haemolyticus (ORSH). The influence of oxacillin and vancomycin on biofilm formation by ORSH strains isolated from fomites was also investigated. METHODS The presence of ORSH on swabs taken from fomite surfaces in a Brazilian hospital was assessed using standard microbiological procedures. Antibiotic susceptibility profiles were determined by the disk diffusion method, and clonal distribution was assessed in pulsed-field gel electrophoresis (PFGE) assays. Minimum inhibitory concentrations (MICs) of oxacillin and vancomycin were evaluated via the broth microdilution method. Polymerase chain reaction (PCR) assays were performed to detect the mecA and icaAD genes. ORSH strains grown in media containing 1/4 MIC of vancomycin or oxacillin were investigated for slime production and biofilm formation on glass, polystyrene and polyurethane catheter surfaces. FINDINGS ORSH strains comprising five distinct PFGE types were isolated from sphygmomanometers (n = 5) and a thermometer (n = 1) used in intensive care units and surgical wards. ORSH strains isolated from fomites showed susceptibility to only linezolid and vancomycin and were characterised as multi-drug resistant (MDR). Slime production, biofilm formation and the survival of sessile bacteria differed and were independent of the presence of the icaAD and mecA genes, PFGE type and subtype. Vancomycin and oxacillin did not inhibit biofilm formation by vancomycin-susceptible ORSH strains on abiotic surfaces, including on the catheter surface. Enhanced biofilm formation was observed in some situations. Moreover, a sub-lethal dose of vancomycin induced biofilm formation by an ORSH strain on polystyrene. MAIN CONCLUSIONS Sphygmomanometers and thermometers are fomites for the transmission of ORSH. A sub-lethal dose of vancomycin may favor biofilm formation by ORSH on fomites and catheter surfaces.